Prenatal fumonisin (FB1) treatment in rats results in minimal maternal or offspring toxicity - Ferguson, SA; StOmer, VEV; Kwon, OS; Holson, RR; Houston, RJ; Rottinghaus, GE; Slikker, W (INTOX PRESS INC, 1997)
To investigate the neurobehavioral and developmental effects of the mycotoxin, FB1, Sprague-Dawley rats were treated with FB1 on gestational days 13-20. In Experiment I, FB1 was obtained from culture material and pregnant rats were gavaged with 0, 0.8 or 1.6 mg/kg. In Experiment 2, pregnant rats were gavaged with purified FB1 at doses of 0, 1.6 or 9.6 mg/kg. Offspring were evaluated on a battery of behavioral tests as well as measures of whole and regional brain weight. There were no effects on maternal weight gain, reproductive outcomes, or offspring body weight through adulthood in either experiment. Complex maze performance, open field and running wheel activity were not altered by prenatal FB1 treatment. In Experiment 2, acoustic startle response was depressed at two ages during the first or second block of 9 trials in males treated with purified FB1. Females exhibited no such alterations. Play behavior at PND 33, but not PND 26, was increased in males prenatally treated with 9.6 mg/kg relative to those treated with 1.6 mg/kg. There were no substantive treatment effects on regional brain weight. These results suggest that doses of less than or equal to 9.6 mg purified FB1/kg and/or less than or equal to 1.6 mg FB1/kg obtained from culture material cause minimal maternal toxicity and produce few developmental functional alterations. In addition, potential FB1-related functional alterations were evident only in males providing further support for a mild sex-specific effect for fumonisin. (C) 1997 Inter Press, Inc.